A novel major QTL underlying grain copper concentration in common wheat (Triticum aestivum L.) - Yiwen Huang; Qiling Zhao; Xiaoying Li; Dan Long; Jian Zeng; Dandan Wu; Lina Sha; Xing Fan; Houyang Kang; Haiqin Zhang; Yonghong Zhou; Yi Wang; et al. (BMC Genomics)
Abstract Grain copper (Cu) concentrations represent a qualitative trait mainly controlled by genetic factors, which may differ between wheat varieties from the Sichuan Basin of China and other areas. However, the differences are poorly understood. Here, we investigated the grain Cu concentration in a remaining heterozygous line population derived from a multiparental recombinant inbred line. The grain Cu concentration varied from 4.25 to 13.44 mg/kg and 3.32 to 7.74 mg/kg over a two-year investigation, and the broad-sense heritability was 0.67. Bulked-segregation analysis revealed three quantitative trait loci on chromosomes 2A (QGr_Cu_Conc-2A), 2B (QGr_Cu_Conc-2B), and 4D (QGr_Cu_Conc-4D). QGr_Cu_Conc-2B is a novel locus, which was further narrowed between KASP-52.32 and KASP-56.57 with an interval of 52.32–56.57 Mb, explaining 17.10% of the phenotypic variation; its potential candidate gene was TraesCS2B03G0196500, encoding a chloroplast thylakoid lumen protein. KASP-52.32 successfully genotyped two common wheat populations, and the grain Cu concentration of CC genotype varieties was significantly higher than that of TT genotype varieties. Meanwhile, the concentrations of chlorophyll and the expression levels of three TaZIP8 and two TaZIP9 in flag leaves were higher in plants with high grain Cu concentration than in plants with low grain Cu concentration. These results provide guidance for understanding the genetic mechanisms underlying grain Cu concentration and may aid in wheat breeding.